Effect of anomalous photoabsorption on parametric X-ray radiation from relativistic electrons; Physics of Atomic Nuclei; Vol. 64, iss. 5 - Gary C. K.; Kaplin V. V. Valery Viktorovich; Nasonov N. N.; Piestrup M. A.; Uglov S. R. Sergey Romanovich (2001, 2001)
Title screen